Recent Advances in the Tunable Optoelectromagnetic Properties of PEDOTs - Ling Zhu; Qi Liu; Yuqian Zhang; Hui Sun; Shuai Chen; Lishan Liang; Siying An; Xiaomei Yang; Ling Zang (Molecules)
Conducting polymers represent a crucial class of functional materials with widespread applications in diverse fields. Among these, poly(3,4-ethylenedioxythiophene) (PEDOT) and its derivatives have garnered significant attention due to their distinctive optical, electronic, and magnetic properties, as well as their exceptional tunability. These properties often exhibit intricate interdependencies, manifesting as synergistic, concomitant, or antagonistic relationships. In optics, PEDOTs are renowned for their high transparency and unique photoelectric responses. From an electrical perspective, they display exceptional conductivity, thermoelectric, and piezoelectric performance, along with notable electrochemical activity and stability, enabling a wide array of electronic applications. In terms of magnetic properties, PEDOTs demonstrate outstanding electromagnetic shielding efficiency and microwave absorption capabilities. Moreover, these properties can be precisely tailored through molecular structure modifications, chemical doping, and composite formation to suit various application requirements. This review systematically examines the mechanisms underlying the optoelectromagnetic properties of PEDOTs, highlights their tunability, and outlines prospective research directions. By providing critical theoretical insights and technical references, this review aims to advance the application landscape of PEDOTs.